Advanced Research on Sprouts and Microgreens as a Source of Bioactive Compounds (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today, researchers are focused on studying and identifying new products that can be beneficial for both food and pharmaceutical purposes. In this context, sprouts and microgreens are widely recognized as functional foods due to their high nutritional value, and in particular, their high bioactive compound content, which is mainly composed of phytochemicals. However, despite extensive research on the germination of species cultivated under optimal conditions, knowledge gaps remain regarding various aspects of sprout and microgreen production. To address this research issue, interdisciplinary collaboration is crucial. This involves the identification of novel species for edible sprout cultivation, the exploration of innovative strategies to stimulate bioactive compound production, and the development of new “nutraceutical” foods. Moreover, it is imperative to elucidate the mechanisms underlying the beneficial effects of the consumption of microgreens. This reprint presents cutting-edge research on sprouts and microgreens, providing valuable insights for the academic community.